Data on the fungal species consumed by mammal species in Australia - S.J. Nuske (Data in Brief, 2017)
The data reported here support the manuscript Nuske et al. (2017) [1]. Searches were made for quantitative data on the occurrence of fungi within dietary studies of Australian mammal species. The original location reported in each study was used as the lowest grouping variable within the dataset. To standardise the data and compare dispersal events from populations of different mammal species that might overlap, data from locations were further pooled and averaged across sites if they occurred within 100 km of a random central point. Three locations in Australia contained data on several (>7) mycophagous mammals, all other locations had data on 1–3 mammal species. Within these three locations, the identity of the fungi species was compared between mammal species’ diets. A list of all fungi species found in Australian mammalian diets is also provide along with the original reference and fungal synonym names.